Therapeutic management in a child with Wilms tumour and radiological features suggesting rupture at the time of diagnosis - Sosnowska-Sienkiewicz, Patrycja; Januszkiewicz-Lewandowska, Danuta; Jończyk-Potoczna, Katarzyna; Gowin, Ewelina; Mańkowski, Przemysław (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Preoperative Wilms tumour rupture has been reported sporadically. But when identified, SIOP (Societe Internationale d’Oncologie Pediatrique) recommends that these patients should be upstaged to the 3rd stage. The purpose of this publication was to present the clinical and radiological features of preoperative tumour rupture in our patient. A 4-year-old girl was treated in the oncology department for a large Wilms tumour. The child presented inconclusive clinical and radiographical features of preoperative tumour rupture. Therefore, standard 4-week preoperative chemotherapy was used. Unfortunately, a tight connection between the cystic part of the tumour and the peritoneum became the cause of tumour rupture during surgery. Not every child who meets the radiological criteria for preoperative tumour rupture should be upgraded. The radiological features of preoperative tumour rupture shouldvery much increase the caution of the surgeon.